(untitled) (Global Journal of Human-Social Science, 2015)
This is a research study examining the perceptions of Lesotho’s rural communities on their contribution towards sustainable rural water supply/RWSsystems. It is a Beneficiary Assessment Approach study and observatory study. In an effort to improve the quality of results that development interventions exhibit, development practitioners engage in beneficiary assessment. The approach gives researchers information that assists in assessing the value on an activity as perceived by its prime users (Salmen, 1995:1). Kumasarisi (2009:2) submits that beneficiary assessment enhances the sustainability of demand-driven development interventions; therefore, it is useful in pointing out bottlenecks to participation faced by target groups. It also uncovers reactions and views that beneficiaries have on the implemented interventions as well as opening up new information that would otherwise not be known.